User-space interaction in commercial architecture: a systematic review of smart environments - Colcas-Contreras, Cinthya Nicole; Rivadeneyra-Huaroto, Karina Ivette; Avalos-Gamez, Leogilda; Solorzano-Mimbela, Christian Jorge (LACCEI, 2025)
Commercial architecture seeks to balance functionality, aesthetics, and user experience in commercial spaces, where the application of innovative strategies is essential to optimize visitor interaction and satisfaction. This systematic analysis, aimed at identifying the architectural elements that enhance the user experience in shopping centers, evaluated scientific studies published between 2019 and 2024 in the academic repositories Scopus and Web of Science, using the PRISMA methodology, selecting 25 relevant studies from an extensive set of 4,070 publications. The results indicate that in 2021 and 2023 there was significant scientific production in this field, with a higher concentration of publications in China, where commercial development is high. Furthermore, lighting, spatial design, and the incorporation of natural elements were identified as key factors in improving user perception and comfort in commercial environments. Regarding the implementation of these strategies, the literature highlights a 36% increase in user satisfaction in commercial spaces with an optimized design. It is concluded that the integration of user-centered architectural approaches contributes to increasing the functionality and attractiveness of commercial establishments, promoting a more comfortable and efficient experience.